Moderating effect of information processing capacity to investment decision making and environmental scanning / Nik Maheran Nik Muhammad ,Muhamad Jantan and Fauziah Md Taib - Nik Muhammad, Nik Maheran; Jantan, Muhamad; Md Taib, Fauziah (Institute of Business Excellent, 2010)
This study will examine the role of information processing capacity in enhancing investment decision quality and environmental scanning relationship. Cross sectional data was collected through a survey and analyzed by means of factor analysis and hierarchical regression analysis. Information processing capacity is only contingent upon technology information in order to affect the quality of investment decision. Method of scanning on the other hand will lead to quality decision only with the inclusion of information processing capacity. Use of convenience sampling may restrict the generalizability of findings. Information processing capacity is needed when scanning technology information to bring about decision quality, thus for technology related matters, firms should be investing in the information processing capacity to produce quality decision. Information processing capacity theory is genuinely new in the literature of investment decision making. This study uses decision as its unit of analysis. Keywords – environmental scanning, decision quality, information processing capacity Paper Type – Research Paper